ASSESSMENT OF PROJECT CHARACTERISTICS AFFECTING RISK OCCURRENCES IN CONSTRUCTION PROJECTS USING FUZZY AHP - Okudan, Ozan; Budayan, Cenk (YILDIZ TECHNICAL UNIV, 2020)
The performance of the construction industry has been widely criticized in the literature due to substantial delays and cost overruns. The dynamic, turbulent, and complex environment of the construction industry can lead to poor performance causing occurrence of numerous risks that can adversely affect the performance of the projects. Risk management plays an important role in the improvement of performance of construction projects. However, performance of risk management is challenging due to limited availability of information, particularly during the risk identification stage. This study aims to identify the characteristics of the construction projects that are critical in the occurrence of the risks. For that purpose, an in-depth literature review was conducted to extract characteristics of the construction projects in the first step of the study. Then, a questionnaire survey was prepared to collect expert opinions. Finally, a MATLAB script was developed inhouse to perform a fuzzy AHP method to analyze the gathered data. The findings show that the contractrelated characteristics, contract type, project value, and construction-related characteristics are the most critical characteristics of construction projects related to risk occurrence cases.
Keywords: Risk management; risk identification; project characteristics; fuzzy AHP; MATLAB; HIERARCHY PROCESS AHP; COMPLEXITY; INNOVATION; PERFORMANCE; DECISION; INDUSTRY; MATRIX; MODEL; Engineering